2013
DOI: 10.1097/cmr.0b013e32835e7713
|View full text |Cite
|
Sign up to set email alerts
|

Difference of interferon-α and interferon-β on melanoma growth and lymph node metastasis in mice

Abstract: Interferon (IFN)-α and IFN-β are type I IFNs which are known to exert an antitumor effect on malignant melanoma. The aim of this study was to evaluate and compare the efficacy of IFN-α2b and IFN-β1a on primary tumor growth and lymph node metastasis, and to examine the mechanisms of lymph node metastasis. The efficacy of IFN-α2b and IFN-β1a was evaluated using a human melanoma xenograft model. We further examined the effect of IFNs on lymphangiogenic growth factors in human melanoma cells. IFN-β1a showed a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
(42 reference statements)
1
13
1
2
Order By: Relevance
“…These tumor extracts were indeed able to block the growth of B16 cells in a type I IFN-dependent manner (Fig. S7), a finding that is consistent with previous reports showing that type I IFNs block proliferation and induce apoptosis of B16 cells (22,23). Together these data indicate that IFN-β is required for the generation of tumor-infiltrating CD8 T cells and for the antitumor activity induced by intratumoral cGAMP.…”
Section: Intratumoral Sting Activation Leads To Systemic Cd8 T-cell-msupporting
confidence: 80%
See 1 more Smart Citation
“…These tumor extracts were indeed able to block the growth of B16 cells in a type I IFN-dependent manner (Fig. S7), a finding that is consistent with previous reports showing that type I IFNs block proliferation and induce apoptosis of B16 cells (22,23). Together these data indicate that IFN-β is required for the generation of tumor-infiltrating CD8 T cells and for the antitumor activity induced by intratumoral cGAMP.…”
Section: Intratumoral Sting Activation Leads To Systemic Cd8 T-cell-msupporting
confidence: 80%
“…Second, type I IFNs may increase CD8 T-cell infiltration into cGAMP-injected tumors (6) and directly promote their survival and proliferation in the tumor microenvironment (24). However, our data suggest that the potent local antitumor efficacy is not explained by increased CD8 T-cell infiltration of cGAMP-injected tumor but rather by a direct inhibitory effect of type I IFNs on the tumor itself (22,23). Representative plots are given (Upper); each symbol represents an independent mouse (Lower).…”
Section: Discussioncontrasting
confidence: 52%
“…Treatment with IFN- α -2b and IFN- β -1a also resulted in decreased proliferation index of human melanoma xenograft tumors as manifest by immunohistochemical staining with Ki-67; again, IFN- β -1a-treated tumors showed less staining with Ki-67 than did IFN- α -2b-treated tumors [37]. In experiments by Garbe et al, IFN- α and IFN- β both showed concentration-dependant inhibition of proliferation of three melanoma cell lines, but IFN- β had the smallest IC 50 for all three cell lines tested.…”
Section: Melanomamentioning
confidence: 99%
“…Kubo et al showed that IFN- β induced apoptosis dose-dependently in 7 melanoma cell lines as well as induced cleavage of caspase 3 in these cell lines [42]. The number of apoptotic cells in human melanoma xenograft tumors was significantly increased in IFN- α -2b- and IFN- β -1a-treated tumors compared with untreated tumors, with IFN- β -1a having a greater apoptotic effect than IFN- α -2b [37]. …”
Section: Melanomamentioning
confidence: 99%
See 1 more Smart Citation